Grafting and Shading—The Influence on Postharvest Tomato Quality - Zoran S. Ilić; Athanasios Koukounaras; Lidija Milenković; Žarko Kevrešan; Aleksandra Bajić; Ljubomir Šunić; Renata Kovač; Elazar Fallik; Jasna Mastilović (Agriculture, 2020)
Interaction of grafting and shading on tomato physical properties and chemical composition after 15 days of storage at 10 °C and 90% relative humidity was investigated in ungrafted and grafted tomato cultivars ‘Optima F1’ and ‘Big beef F1’ grown under shading nets (red and pearl net) and nonshaded conditions. For grafted plants ‘Maxifort’ rootstock was used. The effects of two weeks of storage was statistically significant when taking into account the effects of grafting, shading and variety for all tomato fruit composition parameters, except total phenols. A principal component analysis demonstrated that the changes in tomato fruit traits during the studied storage period were the main source of differentiation in tomato fruit quality. Beside a slight loss of firmness, tomato fruits were generally expected to have lower lycopene, sugar, malic and citric acid contents, higher succinic acid content, more elastic fruit skin and higher ascorbic acid content. Additionally, after storage, fruits from grafted plants had lower total phenol, higher ascorbic acid and higher succinic acid contents compared to fruits from ungrafted plants. Storage diminishes the differences in quality achieved through convenient grafting and shading combinations.